Performance and Durability of One-Cell Module of Biogas-Utilizing SOFC Equipped with Graded Indirect Internal Reformer. Issue 6 (2nd April 2020) - Ayd𝚤n, Özgür; Matsumoto, Go; Kubota, Atsushi; Tran, Dang Long; Sakamoto, Mio; Shiratori, Yusuke
Abstract : Utilization of biogas in Solid Oxide Fuel Cells (SOFCs) is an efficient way of renewable power generation. Despite some technical challenges, biogas can be reformed to H 2 -rich fuel stream in the anodes of SOFCs. However, the reforming rate drastically drops toward the outlet of the flow field due to the rapid conversion of CH 4 (biogas) in the inlet region. As the reforming reactions are endothermic, they cause large temperature gradients along the flow field, so that thermal stresses arise on the SOFC components. This problem can be resolved to an extent via taking the reforming reactions out of the SOFC domain (Indirect Internal Reforming), which however makes the heat transfer from SOFCs to the reforming domain also indirect. From the point of effective thermal integration, this study introduces an innovative indirect internal reforming concept. For totally eliminating the thermal stresses, it is necessary to homogenize the reforming rate, which can be achieved by designing a graded reforming domain. In this paper, we investigate the electrochemical performance and durability of an indirect internal reforming SOFC module featuring a graded reforming domain.